Low cost technology for weed management in rice-1 influence of plant population on the comparative ability of short duration rice on weed communities - Bindy TS (Department of Agronomy, College of Agriculture, 1989)
An experiment was conducted at the college of Agriculture, Vellayani during the Virippu (first crop) season of 1987, to evolve a suitable low cost technology for weed management for short duration transplanted rice cv. Thriveni in split plot design with 16 treatments and 3replications. Monocot weeds predominated throughout the crop growth. Hand weeding twice at 20 and 40 DAT controlled monocot, dicot and total weed population and decreased weed dry matter production. Closer spacing of 10x10 cm and planting 4 seedlings/hill also helped to suppress monocot and dicot wee population and weed dry matter production. Weed control efficiency was highest for hand weeding twice with a spacing of 10x10cm and planting 4 seedlings /hill. Completely weed-free condition resulted in highest tiller production, dry matter production of the crop and productive tillers/m2, followed by hand weeding twice with a spacing of 10x10cm and planting 4 seedlings/hill also resulted in increased tillers/m2, crop dry matter production and productive tillers/m2. Completely weed-free condition and planting 4 seedlings/hill resulted in high leaf area index. Other yield attributes like number of spike lets/panicle, filled grain/panicle, panicle weight and thousand grain weight were also high for completely weed-free condition with a wider spacing of 15x10cm and planting 2seedlings/hill. Grain and straw yields were highest for completely weed –free condition followed by hand weeding twice. Wider spacing of 15x10cm and planting 2 seedlings/hill increased grain yield, while closer spacing of 10x10cm and planting 4 seedlings/hill increased straw yield. Hand weeding twice recorded highest weed index. Nutrient up take by weeds was lowest in weeded treatments, which in turn enhanced the crop uptake. Closer spacing of 10x10cm, and planting 4 seedlings/hill also reduced weed nutrient uptake and increased crop nutrient uptake. Hand weeding twice with a wider spacing of 15x10cm and planting 2seedlings/hill gave the highest net income and cost- benefit ratio